Farmers' participation in cassava technology transfer in the Philippines - Gundaya, Editha A.; Evangelio, Fernando A. (International Center for Tropical Agriculture, 1998)
Experiences gained from past root crop extension activities made PRCRTC realize the importance of clienteles. Participation in technology development and transfer. PRCRTC is now trying to adopt a participatory approach in all cassava technology transfer activities. Results of some of these extension activities shows that farmers. involvement in technology testing and modification and in the over-all decision making process of a project, led to the development of technologies that are better suited to the needs of the clienteles and helps to build up their capacity to manage the project on their own. In 1996 a project was initiated that employs farmer participatory research (FPR) methodologies to transfer soil and water conservation technologies to cassava farmers in Bontoc, south Leyte. This is a cassava growing area where cassava production is increasing due to the establishment of a cassava-based feedmill, as well as the entry of San Miguel Corporation, which buys large volumes of dried cassava chips for export. A preliminary survey about the farmers' knowledge, attitude and practices concerning soil conservation has already been conducted with 91 cassava farmers as respondents. The majority (75%) of the farmers realized the damage that would occur on continuously cultivating hilly areas, but only less than 50% are actually trying to control erosion using various methods they learned from different sources. Around 65% of the respondents, however, expressed their interest in learning soil conservation methods that would be more effective than the methods presently used. The information given by the farmers is now used as the basis for conducting other FPR activities in Bontoc.